2021
DOI: 10.3390/ijerph182211969
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Telemedicine and eHealth in Surgery during the SARS-CoV-2 Pandemic

Abstract: SARS-CoV-2 has hampered healthcare systems worldwide, but some countries have found new opportunities and methods to combat it. In this study, we focused on the rapid growth of telemedicine during the pandemic around the world. We conducted a systematic literature review of all the articles published up to the present year, 2021, by following the requirements of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. The data extracted comprised eHealth and telemedicine in su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…COVID-19 continues to transform the telemedicine landscape with breathtaking speed in Europe and America, contrary to the reluctance that existed before the pandemic [ [61] , [62] , [63] , [64] , [65] ]. Telemedicine developments and adoption had been happening at a slow pace before the pandemic [ 61 ].…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…COVID-19 continues to transform the telemedicine landscape with breathtaking speed in Europe and America, contrary to the reluctance that existed before the pandemic [ [61] , [62] , [63] , [64] , [65] ]. Telemedicine developments and adoption had been happening at a slow pace before the pandemic [ 61 ].…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Recently, more and more other studies discussed the implications of telemedicine in orthopedics from various aspects. [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the first wave of the COVID-19 pandemic, technology played an important role in providing safe healthcare, where telemedicine was the most commonly used technology, followed by videoconferencing (Zoom) and social media platforms (WhatsApp) (Abd-Alrazaq et al, 2021). Similarly, telemedicine and eHealth created innovations and a revolution in providing healthcare to patients with surgery globally (Taha et al, 2021). A review reported that the use of m-Health apps is a suitable method, bypassing the costly infrastructure, and is considered more accessible in terms of providing quality health care services, especially in the oncology services (Mehdizadeh et al, 2019).…”
Section: Implications Of the Review Findingsmentioning
confidence: 99%